A comparative study of student performance in all-ceramic crown preparation by clinical-phase students - Abdulkarim H. Alshehri; Mohammed M. Al Moaleem; Abdullah Ahmed Meshni; Thrya S. Gadah; Nasser M. Alahmari; Nassreen H. Albar; Hafiz Ahmed A. Adawi; Bandar M. A. AL-Makramani; Mosa A. Shubayr; Kulashekar Reddy Nandalur (BMC Medical Education)
Abstract Background Given ongoing discussions about potential gender disparities in clinical skill assessments within dental education, this study aimed to evaluate whether an analytic rubric could provide objective, equitable evaluation of all-ceramic crown preparations among male and female dental students. Materials and methods An analytical rubric for the evaluation of all-ceramic preparation steps was utilized in a clinical course study with two evaluators. The scoring was created on a 5-point scale for three parameters (preparation, tissue management, final impression) and a 4-point scale for the time management parameter, and the overall score was considered as 39 points. Variances in rubric parameter scores among male and female students were examined via an independent t test. Additional tests, such as the kappa test and Pearson’s correlation coefficient, were utilized to measure the connotations between the cumulative grade point average (CGPA), evaluators, and gender of the participants. The value of p was set as < 0.05 and considered statistically significant. Results The overall score was very good and almost equal for males (31.03) and females (31.00), with no statistically significant differences in most rubric parameters between students or as recorded by both evaluators (p > 0.05). The highest value was for tissue management (4.38 males, 4.22 females), and the lowest value was for time management (3.50 males, 3.44 females). Amongst the other assessed parameters, only the final impression parameter was significantly different (p = 0.006). Inter-evaluator agreement analysis exposed changing levels of agreement among the assessors. High and strong positive correlations were documented among numerous rubric parameters, but CGPA had a weak, nonsignificant correlation with their clinical performance (p = 0.160). Conclusion The findings demonstrate that structured analytic rubrics can yield consistent, gender-neutral assessments of clinical skills, supporting their use in promoting equitable competency evaluation in dental education. This is particularly relevant for institutions with gender-separated training programs, where standardized tools help mitigate potential biases.